Balkan village - Sanders, Irwin T. (Irwin Taylor), 1909-2005 (University of Kentucky Press, 1949)
In the Balkans today Communism, with its dynamic drive for power and sense of mission, is charging against the Balkan peasant mass, a patient, religious, tradition-bound people tilling their beloved soil. Dragalevtsy, the Balkan village described by Mr. Sanders, brings this struggle into focus. The book details the way of life of a tranquil rural folk clinging to a Bulgarian mountainside, in the shadow of a twelfth- century monastery -- their history, economic system, marriage customs, family life, and reluctant yielding to the ways of the western world. On September 6, 1944, Dragalevtsy peasa.